Визначення ризиків ампутації та смерті у пацієнтів із синдромом діабетичної стопи та критичною ішемією нижніх кінцівок - Горобейко, М. Б. (Clinical Endocrinology and Endocrine Surgery, 2014)
Using Cox regression dependence of the probability of amputation and probability of death among patients with critical limb ischemia with diabetic foot syndrome from the base value of ТсРО2 was analyzed. Determined that the conventional boundary critical ischemia level ТсРО2 relatively high risk of amputations can be considered at level ТсРО2 <14 mm Hg. At this level and less the risk of amputation was statistically higher. Risk of low amputation in patients increases with ТсРО2 <20 mm Hg. Mortality among patients had been statistically higher if ТсРО2 was <20 mm Hg. Mortality in groups where the figure is less than had virtually no difference. It is expedient to revise the criteria of critical ischemia to level of ТсРО2 20 mm Hg.